SWARM OF AMPHIPODS ATYLUS MINIKOI (WALKER) IN THE SHALLOW WATERS OF THE KARWAR BAY - Naomi, T S (Indian Journal of Fisheries, 2011)
The occurrence of a swarm of arophipods Atytus minikoi (Walker) in theshallow waters is reported for the fir'st time from the seas around India.